A cluster randomised intervention trial of asthma clubs to improve quality of life in primary school children: the School Care and Asthma Management Project (SCAMP). Issue 8 (22nd July 2005) - Patterson, E E; Brennan, M P; Linskey, K M; Webb, D C; Shields, M D; Patterson, C C
Abstract : Aim: To evaluate the effectiveness of a programme of asthma clubs in improving quality of life in primary school children with asthma. Methods: A cluster randomised intervention trial was undertaken in 22 primary schools within the urban area of south and east Belfast, Northern Ireland. Schools were randomised in pairs to immediate or delayed groups. The study subjects comprised 173 children aged 7–11 years whose parents had notified the school of their asthma diagnosis. Children attended school based weekly clubs over an 8 week period. The main outcome measures were the interview administered Paediatric Quality of Life Questionnaire scores, ranging from 1 (worst) to 7 (best), spirometry, and inhaler technique. Results: Over 15 weeks, small but non-significant improvements in the overall quality of life score (mean 0.20; 95% confidence interval (CI) −0.20 to 0.61) and in each of its three components, activity limitation (0.20; −0.43 to 0.84), symptoms (0.23; −0.23 to 0.70), and emotional function (0.17; −0.18 to 0.52), were observed in the immediate compared with the delayed group. Inhaler technique at week 16 was markedly better in the immediate group, with 56% having correct technique compared with 15% in the delayed group. No significant effect of the intervention on spirometry results could be demonstrated. Conclusion: This primary school based asthma education programme resulted in sustained improvements in inhaler technique, but changes in quality of life scores were not significant.